Allele Frequencies of 15 AmpFISTR Identifiler loci in the Nepalese population - Jha, Dinesh Kumar; Gonzalez, Luis Javier Martinez; Rijal, Jiwan Prasad; Tuladhar, Bhinu Shova; Chhetri, Nirajan Thapa (Scientific World, 2012)
Allele frequencies for the 15 STR loci in the AmpFlSTR® Identifiler® and statistical parameters were estimated from a sample of 233 unrelated individuals from different area of Nepal. A total of 161 alleles were found, with corresponding allelic frequencies ranging from 0.0021 to 0.4077. The MP, PD, PIC, PE, TPI, Ho and He ranged from 0.0282 to 0.1511, 0.8489 to 0.9717, 0.6478 to 0.8700, 0.4546 to 0.7631, 1.7651 to 4.3148, 0.7167 to 0.8841 and 0.7009 to 0.8833 respectively. Deviations from the Hardy–Weinberg Equilibrium were observed for D16S539, D18S51, D21S11 and TPOX Markers. One new allele has been detected in the process. Scientific World, Vol. 10, No. 10, July 2012 p20-23 DOI: http://dx.doi.org/10.3126/sw.v10i10.6856